2019
DOI: 10.3390/su11185003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Spatial and Temporal Characteristics of Citizens’ Mobility Based on E-Bike GPS Trajectory Data in Tengzhou City, China

Abstract: Environmentally friendly shared transit systems have become ubiquitous at present. As a result, analyzing the ranges and tracts of human activities and gatherings based on bike share data is scientifically useful. This paper investigates the spatial and temporal travel characteristics of citizens based on real-time-extracted electric bikes (e-bikes) Global Positioning System (GPS) data from May to July in 2018 in the central area of Tengzhou City, Shandong Province, China. The research is conducive for the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Previous studies did a lot of work on travel mobility, heterogeneity, and rebalance [28,32,33]. Li and Dai et al argued that the rides peak hour was 18:00 and concentrated in the core area of cities [34]. Zheng et al studied Mobike bike sharing system in Beijing and found that the unbalance of nodes in mobility OD network follows a power law distribution [35].…”
Section: Literature Review 21 Spatial-temporal Characteristics Of Bik...mentioning
confidence: 99%
“…Previous studies did a lot of work on travel mobility, heterogeneity, and rebalance [28,32,33]. Li and Dai et al argued that the rides peak hour was 18:00 and concentrated in the core area of cities [34]. Zheng et al studied Mobike bike sharing system in Beijing and found that the unbalance of nodes in mobility OD network follows a power law distribution [35].…”
Section: Literature Review 21 Spatial-temporal Characteristics Of Bik...mentioning
confidence: 99%
“…Many micromobility issues have been addressed using GIS, such as micromobility equity [43], potentiality for micromobility to replace cars [44], spatiotemporal characteristics [45], the role of micromobility in first/last mile problem [46], whether micromobility complements or competes with public transit [47], and changes in micromobility usage before and after COVID-19 lockdowns [48]. Improper micromobility parking causing blocked access is one of the most common concerns of micromobility and has been addressed by many authors [49,50].…”
Section: Micromobilitymentioning
confidence: 99%
“…In [10], a Mixed-Path Size logit model was devised to analyse the route choice decisions of E-bike users in the Netherlands. The work in [9] carried out analysis of both spatial and temporal characteristics of E-bike user' mobility in Tengzhou City, China. In [11], a trip purpose imputation framework was developed to assist in trip purpose prediction based on the trip records of different micro-mobility tools before and during the COVID-19 pandemic period in Zurich, Switzerland, and finally in [12], a hierarchical clustering method was employed to address the issue of free-floating bike-sharing parking in Beijing, China.…”
Section: Introductionmentioning
confidence: 99%